Age at Sexual Debut as a Determinant of HPV Infection in Women with Clinically Normal Cervix in Indonesia - Utami, Tofan Widya; Nuranna, Laila; Purwoto, Gatot; Indarti, Junita; Firdaus, Najmarani Devi; Oktalia, Arisda; Sulastri, Nuni; Kekalih, Aria (Indonesian Socety of Obstetrics and Gynecology, 2026)
Objectives: This study examined the association between sexual debut and HPV infection in Indonesian women with a clinically normal cervix, contextualized within the Sustainable Development Goals (SDGs). Methods: This prospective cohort study utilized primary data from structured interviews and gynecological exams conducted by the Female Cancer Program (FCP) team across public and private health providers in Jakarta (January 2012–July 2018). Cervical cancer risk factors, including early sexual debut, were analyzed using odds ratios (ORs). Results: A total of 1,390 women with a clinically normal cervix were enrolled in this study, with 52 (3.7%) testing positive for HPV-DNA. Statistical analysis indicated an odds ratio (OR) of 1.176 (95% CI: 0.598–2.316, p = 0.601) for early sexual debut. Conclusion: This study showed that there was an insignificant association between sexual debut and HPV infection in clinically normal cervix. According to the SDGs, early sexual debut and cervical cancer are highly associated. In order to meet the SDGs by 2030, more research is required to validate this finding and assess additional co-factors connected to cervical cancer.